66.2k views
0 votes
XB−→− is the angle bisector of ∠AXC. m∠AXB=23°

User Ramirez
by
5.2k points

1 Answer

3 votes

Answer:

∠AXC = 46°

∠BXC = 23°

Explanation:

If XB is the angle bisector of ∠AXC then XB bisects ∠AXC t at X. Hence;

∠AXC = ∠AXB+∠BXC and ∠AXB= ∠BXC

The equation becomes

∠AXC = ∠AXB+∠AXB

∠AXC = 2∠AXB

Given

m∠AXB=23°

Substitute the given angle into the expression above to get ∠AXC since we are not told what to find but we can as well find ∠AXC

∠AXC =2(23)

∠AXC = 46°

Also note that since ∠AXB= ∠BXC, then ∠BXC will be 23°

User Matt Brody
by
4.8k points